JASA TAHLIL PRABAYAR DESA KAMPUNG DALEM KOTA KEDIRI - Dyah Ayu Setiyarini, dkk (Qawanin: Jurnal of Economic Syaria Law, 2017)
In Indonesia it appears logical, it has a lot of "tahlil". Even has become flesh among Muslims. Before Islam came there was no "tahlil". It used to be people's habits if someone dies after neighbors gathered at the funeral home and sometimes they gamble to stay up until morning. Then came the cleric called a "Wali Songo" to change the habits of people get together and play gambling be gathered to pray for the deceased which called "tahlilan". "Tahlil" comes from the word "" ھلل - یھلل - تھلیلاwhich means to read lafadz " "لاإلھإلاااللهwhich means there is no god but Allah. That is the purpose of reading “tahlil” was read verses or dhikr of Allah. The rituals like this is not just a "tahlil ", but there are also" Manakib "," Istighosah "and others.But in so far is that all based on the power of money. Many of the chairman of the "tahlil" put a price on his services. Sometimes there are individuals and there are also tahlil institutions service providers. Usually this tahlil services performed for seven days after someone dead. But there is also held because there are certain necessities such as in calling for a single day during the ritual forty days of death, hundred days of death, a thousand days of death, birth of a baby, seven months of pregnancy and others. In taking wages in terms of worship is a lot of disagreement among scholars,there should be and there should not be. And both have a legal basis tosupport this. Keywords: tahlil, manakib, istighosah